Molecular determinants within the C-termini of L-HDAg that regulate hepatitis D virus replication and assembly - Guo, Hongbo; Li, Qiudi; Li, Chunyang; Hou, Yao; Ding, Yibo; Liu, Dan; Ni, Yi; Tang, Renxian; Zheng, Kuiyang; Urban, Stephan; Wang, Wenshi (JHEP reports, 2024)
Background & Aims - Hepatitis D virus (HDV) is the causative agent of chronic hepatitis delta, the most severe form of viral hepatitis. HDV encodes one protein, hepatitis delta antigen (HDAg), in two isoforms: S- and L-HDAg. They are identical in sequence except that L-HDAg contains an additional 19-20 amino acids at its C-terminus, which confer regulatory roles that are distinct from those of S-HDAg. Notably, these residues are divergent between different genotypes. We aimed to elucidate the molecular determinants within the C-termini that are essential for the regulatory role of L-HDAg in HDV replication and assembly. - Methods - Northern blot, reverse-transcription quantitative PCR, and a newly established HDV trans-complementary system were used in this study. - Results - C-termini of L-HDAg, albeit with high sequence variation among different genotypes, are interchangeable with respect to the trans-inhibitory function of L-HDAg and HDV assembly. The C-terminus of L-HDAg features a conserved prenylation CXXQ motif and is enriched with proline and hydrophobic residues. Abolishment of the CXXQ motif attenuated the inhibitory effect of L-HDAg on HDV replication. In contrast, the enrichment of proline and hydrophobic residues per se does not modify the trans-inhibitory function of L-HDAg. Nevertheless, these residues are essential for HDV assembly. Mechanistically, prolines and hydrophobic residues contribute to HDV assembly via a mode of action independent of the prenylated CXXQ motif. - Conclusions - Within the C-terminus of L-HDAg, the CXXQ motif and the enrichment of proline and hydrophobic residues are all essential determinants of L-HDAg’s regulatory roles in HDV replication and assembly. This intrinsic viral regulatory mechanism we elucidated deepens our understanding of the unique life cycle of HDV. - Impact and implications - Hepatitis D virus (HDV) encodes one protein, hepatitis delta antigen (HDAg), in two isoforms: S- and L-HDAg. They are identical in sequence except that L-HDAg contains an additional 19-20 amino acids at its C-terminus. This C-terminal extension in L-HDAg confers regulatory roles in the HDV life cycle that are distinct from those of S-HDAg. Herein, we found that C-termini of L-HDAg, although with high sequence variation, are interchangeable among different HDV genotypes. Within the C-terminus of L-HDAg, the prenylation motif, and the enrichment of proline and hydrophobic residues are all essential determinants of L-HDAg’s regulatory roles in HDV replication and assembly.